Diagnostic significance of immunological parameters in predicting the development of pneumonia in adult patients with measles - O. V. Riabokon; S. O. Bilokobyla; O. O. Korniienko; Yu. Yu. Riabokon (Zaporozhye State Medical University, 2024)
The aim of the study is to determine the diagnostic significance of immunological parameters in predicting the development of pneumonia in adult patients with measles. Material and methods. The study examined 88 patients aged 21 to 55 years diagnosed with measles according to the World Health Organization's criteria (2013). Enzyme-linked immunosorbent assay (ELISA) was used to determine IgG levels to the measles virus (Vircell Microbiologists, Spain) and the levels of interferon-γ (IFN-γ) (Invitrogen, Austria). Statistical analysis was conducted using Statistica 13 for Windows (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. According to the results of the study, it was found that upon hospitalization on the 4.8 ± 0.2 day of the disease, 71.6 % of patients were seropositive for IgG to measles virus. The development of measles pneumonia was associated with the lowest level of IgG to measles virus (p < 0.01). When the level of IgG to measles virus at hospitalization of adult patients was ≤20.26 optical units, the probability of developing measles pneumonia was significant (AUC = 0.650, p = 0.016). In adult patients with measles, the serum IFN-γ level at the height of the disease was higher (p < 0.05) than in healthy individuals. Upon hospitalization on the 4.8 ± 0.2 day of the disease, the level of IFN-γ in the setting of pneumonia was the highest (p < 0.05), exceeding the corresponding parameter in patients without complications. The level of IFN-γ at hospitalization >1.90 pg/ml was diagnostic for predicting the likelihood of pneumonia (AUC = 0.643, p = 0.038). The authors present their clinical observation, which demonstrates the informative value of using the established immunological parameters in clinical practice to predict the likelihood of pneumonia in adult patients with measles. Conclusions. The diagnostic significance of such immunological parameters as IgG to measles virus and IFN-γ in predicting the development of pneumonia in adult patients with measles at the time of hospitalization has been proved. Our clinical observation demonstrates the informativeness of the established prognostic markers.